Variasi Kadar Kacang Almond untuk Pembuatan Susu sebagai Alternatif Media Kontras Oral Magnetic Resonance Cholangio Pancreatography (MRCP) - Erfansyah, Muhammad; Fatimah, Fatimah; Septiana, Ana (Poltekkes Kemenkes Semarang, 2025)
Background: Exploring the manganese content in almond milk and the efficiency of the analytical method used in this measurement. This research aims to understand how much manganese is contained in almond milk and how mixing almonds with milk affects the mineral content and is used for MRCP examination.Methods: The research design is a true experimental design with quantitative methods. This design has a control group and a selected experimental group. Using almonds and manganese chloride (MnCl2) as a control. AAS testing to determine manganese content.Results: The research results showed that the manganese content in almond milk mixed with a ratio of 150 ml of milk per 150 grams of almonds was 0.01570 mg/L. This shows that almond milk contains amounts of manganese that can contribute to humans' daily mineral intake. In addition, this study also noted that almond milk with this mixture achieved a significant signal suppression ratio, namely 43.3/1.9. This signal suppression ratio is an indicator of efficiency or success in a particular research or testing process.Conclusions: The use of almond milk can be used as an oral negative contrast medium and can be used for Magnetic Resonance Cholangiopancreatography (MRCP) examination.